Ratchaphatsadu Land Law and the administration of Ratchaphatsadu Land - Srisawat, Pitchasinee (Academic Journal Phranakhon Rajabhat University, 2020)
Thailand has the law about Ratchaphatsadu land which has been enforced for a long time until Ratchaphatsadu Land Act B.E. 2562 was published in the Government Gazette on 9 March B.E.2562 This Act has determined the type of Ratchaphatsadu Land and The immovable property that is not Ratchaphatsadu Land. The Treasury Department has duty to govern, supervise and maintain Ratchaphatsadu Land, and clearly define matters relating to the administration of Ratchaphatsadu Land, such as the preparation of Ratchaphatsadu Land registration and the recall of the Ratchaphatsadu Land Determination of powers and duties in administration, maintenance and use of Ratchaphatsadu Land. Therefore, Ratchaphatsadu Land Act B.E. 2562 is a law that clearly stipulates the administration of Ratchaphatsadu Land , the procurement of Ratchaphatsadu Land, this law stipulates the agencies are responsible for the administration and maintenance of reserved or restricted land for the benefit of a particular land or reserved or restricted land for the benefit of the government according to the law and this act has the regulations for managing the Ratchaphatsadu Land outside the Kingdom of Thailand and the property outside the Kingdom of Thailand in accordance with the economic, social and government policies that maintains the Ratchaphatsadu Land for the benefit of the state.